Digitalization of Taxation and Taxpayer Compliance - Ni Putu Desriana Dewi; Gede Sri Darma (Dinasti Publisher, 2024)
The purpose of this study Digitalization of Taxation and Taxpayer Compliance is to re-examine how digitalization, attitude, social norms and perceived behavioral control affect taxpayer compliance based on a phenomenon that occurs every year in almost all tax offices in Indonesia, that is, the large number of taxpayers who come directly to the tax office, even with the help of digital tax services. Through quantitative research methods with SEM analysis techniques, the results of this study show that three of the four variables have a significant effect on taxpayer compliance. However, pereceived control behaviour were not found to have a significant effect on compliance. The results of this study can be used as input for decision-makers in the implementation of regulations, especially in tax education and digital tax services in optimizing the digitization of taxation to increase taxpayer compliance.